2022
DOI: 10.1097/mcp.0000000000000883
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic bronchoscopy for malignant central airway obstruction: impact on quality of life and risk-benefit analysis

Abstract: Purpose of reviewMalignant central airway obstruction (CAO) is a common complication in cancer and confers significant symptom burden and reduction in quality of life. Multiple bronchoscopic interventions exist for malignant CAO. In this review, we discuss the role of therapeutic bronchoscopy in the management of malignant CAO, emphasizing its impact on symptom control and quality of life while balancing the risks and benefits of intervention. Recent findingsSignificant practice variations exist among practiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Recent data also support the idea that therapeutic bronchoscopy may enable more definitive cancer treatment with further improving patient outcomes. Therefore, bronchoscopy can be safely used for therapeutic purposes in malignant central airway obstruction with effective outcomes (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Recent data also support the idea that therapeutic bronchoscopy may enable more definitive cancer treatment with further improving patient outcomes. Therefore, bronchoscopy can be safely used for therapeutic purposes in malignant central airway obstruction with effective outcomes (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Among the various airway pathologies that may require stent placement, malignant airway obstruction is the most common [5,6]. Most commonly a result of primary lung cancer, airway obstruction can also develop from pulmonary metastases or intrathoracic complications from other malignancies, including lymphoma or breast, esophageal, colon, and renal cell carcinomas [1].…”
Section: Indications For Stent Placementmentioning
confidence: 99%
“…Airway obstruction generally consists of three main types: intrinsic (or endoluminal), extrinsic (or extraluminal), and mixed obstruction [5,6]. For intrinsic obstructions, which are most commonly a result of endoluminal tumor growth, therapeutic bronchoscopic interventions with the application of various ablative therapies can often provide adequate airway recanalization without stent placement [10][11][12].…”
Section: Indications For Stent Placementmentioning
confidence: 99%
“…Similarly, Oviatt et al did not find a significant difference overall in HrQOL measured in 19 patients who underwent TB for MCAO despite 84% of patients maintaining airway patency ( 20 ). However, larger studies have demonstrated HrQOL improvement after TB for MCAO in both prospective and retrospective fashion ( 10 , 11 , 17 , 26 ). A retrospective study of 1,115 patients by Ost et al found that Greater baseline dyspnea was associated with improved HrQOL whereas lobar obstruction was associated with smaller improvements ( 10 ).…”
Section: Hrqolmentioning
confidence: 99%